One-Part Alkali-Activated Slag/Fly Ash for Soft Soil Stabilization: Freeze-Thaw Durability Assessment and Mechanism Elucidation - Li Liu; Mengjie Yuan; Xiyao Zheng; Jun Wu (Buildings, 2025)
The climate in extremely cold regions is becoming increasingly unstable, resulting in more frequent freeze-thaw cycles. These cycles significantly degrade the mechanical properties of soft soil foundations, reducing their bearing capacity and ultimately compromising the safety and lifespan of construction and infrastructure. To mitigate these effects, soil stabilization technology is commonly employed to reinforce soft soil in cold regions. However, evaluating the durability of stabilized soft soil, particularly its resistance to freezing in extremely cold environments, remains a critical challenge. This study investigates the use of industrial waste raw materials, such as slag and fly ash (FA), in combination with a solid alkali activator (NaOH), to develop one-part alkali-activated cementitious materials (ACMs) for soft soil stabilization. The effects of different raw material ratios, freeze-thaw temperatures, and the number of freeze-thaw cycles on the freezing resistance of one-part alkali-activated slag/FA (OP-ASF) stabilized soft soil were examined. Mass loss, unconfined compressive strength (UCS), and pH value were conducted to assess soil deterioration and structural integrity under freeze-thaw conditions. Additionally, microstructure analysis was conducted using scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDS) and X-ray diffraction (XRD) to analyze hydration product formation and internal structure characteristics. Image-pro plus (IPP) was also employed for structure looseness evolution, providing deeper insights into the freezing resistance mechanisms of OP-ASF stabilized soft soil. The results indicated that as the freezing temperature decreases and the number of freeze-thaw cycles increases, both mass loss and UCS loss become more pronounced. When the ratio of slag to fly ash was optimized at 80:20, OP-ASF stabilized soft soil exhibited the highest freezing resistance, characterized by the lowest mass loss and UCS loss, along with the highest UCS and pH value. Furthermore, structure looseness remained at its lowest across all freeze-thaw temperatures and cycles, highlighting the beneficial role of slag and FA in OP-ASF. These findings contribute to the advancement of sustainable and durable construction materials by demonstrating the potential of one-part alkali-activated slag/fly ash for stabilizing soft soils in seasonally frozen regions.